2022
DOI: 10.1007/s11764-022-01246-4
|View full text |Cite
|
Sign up to set email alerts
|

Looking at individual symptoms: the dynamic network structure of depressive symptoms in cancer survivors and their preferences for psychological care

Abstract: Purpose The majority of depressed cancer survivors do not receive psychological care, possibly because offered care does not align with their experiences and preferences. We examined (1) which depressive symptoms cancer survivors would like to receive psychological care for; (2) how distinct depressive symptoms are related to each other in the contemporaneous and temporal network of depressive symptoms; and (3) whether survivors’ care needs correspond to the interconnectedness of these specific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Wilson and Cleary’s health-related quality of life model, highlights the interconnectedness of symptom status, which influences functional health, which influences the general health perception, which consequently influences the overall quality of life 136 . Applying this model to our findings may suggest that improving quality of life in individuals with chronic conditions can be achieved by reducing fatigue symptoms through PA 51 . This perspective could indicate the potential of PA to positively impact the overall well-being and functioning of individuals with chronic conditions.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Wilson and Cleary’s health-related quality of life model, highlights the interconnectedness of symptom status, which influences functional health, which influences the general health perception, which consequently influences the overall quality of life 136 . Applying this model to our findings may suggest that improving quality of life in individuals with chronic conditions can be achieved by reducing fatigue symptoms through PA 51 . This perspective could indicate the potential of PA to positively impact the overall well-being and functioning of individuals with chronic conditions.…”
Section: Discussionmentioning
confidence: 78%
“…PA interventions targeting fatigue often focus on one specific chronic condition rather than addressing the symptom itself, despite its prevalence in various chronic conditions. Interventions targeting fatigue are essential in the onset of symptoms and could align with individuals’ needs 51 . Therefore, gaining a better understanding of fatigue transdiagnostically, could provide valuable insights into the relationship between PA and fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…35 A study in cancer survivors with depressive symptoms combined data on supportive care needs with estimated temporaneous symptom networks. 36 The authors identified high scores on fatigue and worrying to be strongly predicted by their scores at the previous time point, suggesting self-reinforcing loops. Also, patients expressed a supportive care need for fatigue, feeling down, little enjoyment, and sleep problems, of which feeling down and little enjoyment were also the most central nodes in the network.…”
Section: Discussionmentioning
confidence: 95%
“…Psychological symptoms including anxiety, depression, stress, fatigue, and mood changes are well known to negatively affect the quality of life in cancer patients [ 101 , 102 ]. As noted above, cancer patients participating in clinical trials of CBD or CBD/THC have reported improvements in assessments of these symptoms.…”
Section: Anxiety/depressionmentioning
confidence: 99%